Method for preparing C2H4 by electrochemical reduction of CO2
By constructing Cu-Ni alloy nanowires in situ on the gas diffusion electrode, the problem of high kinetic barrier of CO2 to C2H4 was solved, and efficient and stable C2H4 conversion was achieved, and the Faraday efficiency and current density were significantly improved.
Patent Information
- Application Number
- CN202411702478.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The prior art is difficult to efficiently convert CO2 into polycarbon products such as ethylene (C2H4), especially due to the high kinetic barrier of the C-C coupling process on the surface of Cu catalyst and the stable adsorption of intermediates, resulting in low conversion efficiency.
C2H4 was prepared by electrochemical reduction of CO2 by using in-situ growth Cu-Ni alloy nanowires as gas diffusion electrodes. The method includes constructing a Cu-Ni film by electrodeposition on carbon paper, then converting it into hydroxide nanowires under alkaline conditions, annealing to form oxide nanowires, and finally obtaining a Cu-Ni alloy nanowire gas diffusion electrode through electrochemical reduction.
The efficient conversion of C2H4 was achieved, the Faraday efficiency reached 46.98%, and the current density reached 231.81mA/cm2, which significantly improved the selectivity and stability of C2H4 and exceeded the performance of bare copper nanowires.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to an electrochemical reduction method for CO 2 Preparation C 2 H 4 The method belongs to the field of electrocatalysis technology. Background Art
[0002] The electrocatalytic process converts CO 2 Converting carbon dioxide into valuable industrial products is an important approach to sustainable development. In particular, reducing carbon dioxide to fuels and industrial raw materials can not only alleviate energy problems, but also achieve the closure of the carbon cycle and provide a viable solution for carbon neutrality. Therefore, it is very important to design and manufacture high-performance electrocatalysts for specific high-value-added products. In recent years, researchers have made significant progress in the development of electrocatalysts, ultimately achieving carbon monoxide (CO), formic acid (HCOOH), methane (CH 4 ), and other C1 products. 2 Converted into ethylene (C 2 H 4 ) and ethanol (C 2 H 5 OH) remains a formidable challenge. 2 H 4 Known for its high energy density, copper plays an important strategic role as a key compound in industrial gases. Metal catalysts, including Au, Ag, Sn, Ni and Pb, show a tendency to generate C1 products. Uniquely, copper-based catalysts have demonstrated the ability to convert CO to C1 products through a CC coupling process. 2 Convert to C 2 H 4 However, C 2 H 4 The efficient conversion of Cu is hampered by the high kinetic barrier of CC coupling process on the Cu catalyst surface and the stable adsorption of key intermediates. There are many strategies, such as crystal surface regulation, single atom, defect engineering, etc., to regulate the physical or chemical properties of catalysts to improve the adsorption and desorption processes. The researchers designed a series of alloy catalysts such as Au-Cu and Ag-Cu, which greatly improved the Cu metal on C by strengthening CC coupling through CO spillover effect. 2 H 4 Selectivity and efficiency in production. Nevertheless, in order to reduce application costs, it is necessary to free ourselves from the dependence on precious metals. Researchers have advanced the development of alloy materials such as Cu-Zn, Cu-Sn and Cu-Pd, but the catalytic results have not met high expectations. The present invention is proposed. Summary of the invention
[0003] The present invention aims to provide an electrochemical reduction method for CO 2 Preparation C 2 H 4 The method uses in-situ grown Cu-Ni alloy nanowires as gas diffusion electrodes with excellent C 2 H 4 Selectivity and stability.
[0004] The Cu-Ni alloy nanowires and non-precious metals used in the present invention are constructed in situ on the gas diffusion layer (GDL). Specifically, the construction method is as follows: S1. Immerse carbon paper in CuSO 4 、NiCl 2 、NiSO 4 Electrodeposition is performed in a mixed solution to obtain a Cu-Ni film; S2, the Cu-Ni film reacts under alkaline conditions to obtain Cu-Ni hydroxide nanowires; S3, annealing the Cu-Ni hydroxide nanowires to obtain Cu-Ni oxide nanowires; S4. The Cu-Ni oxide nanowires are electrochemically reduced to obtain in-situ grown Cu-Ni alloy nanowires.
[0005] In step S1, the mixed solution is prepared from 0.1 M citric acid buffer.
[0006] In step S1, in the mixed solution, the CuSO 4 The concentration of NiCl is 0.05M-0.15M. 2 The concentration of NiSO is 0.03M-0.08M. 4 The concentration is 0.03M-0.08M.
[0007] In step S1, the electrodeposition time is 1500-2000 s, and the obtained film is completely dried in a nitrogen atmosphere.
[0008] In step S2, the alkaline condition is NaOH and (NH 4 ) 2 S 2 O 8 The aqueous solution, the concentration of NaOH is 45-50g / L, the (NH 4 ) 2 S 2 O 8 The concentration is 20-25g / L.
[0009] In step S2, the reaction temperature is 2-8°C and the reaction time is 0.3-0.6h.
[0010] In step S3, the annealing temperature is 150-200° C., the time is 0.5-2 h, and the annealing is performed in a muffle furnace.
[0011] In step S4, the electrochemical reduction is performed in a flowing electrolytic cell using a 0.50 M sodium sulfate solution as an electrolyte, and a potential of -1.0 V (vs Ag / AgCl sat. KCl) is applied for the electrochemical reduction.
[0012] Electrochemical reduction of CO using the Cu-Ni oxide nanowires 2 Preparation C 2 H 4 The method comprises the following steps: The Cu-Ni alloy nanowires are used as gas diffusion electrodes to electrochemically reduce CO 2 Get C 2 H 4 .
[0013] Preferably, the electrochemical reduction is performed in a flow electrolysis cell.
[0014] Preferably, a three-electrode system is provided in the flow electrolytic cell, wherein the Ag / AgCl electrode serves as a reference electrode, the iridium oxide mesh serves as a counter electrode, and the Cu-Ni alloy nanowire serves as a working electrode.
[0015] The method of the present invention uses in-situ grown Cu-Ni alloy nanowires as gas diffusion electrodes to electrochemically reduce C 2 H 4 and CO, producing C 2 H 4 The Faradaic efficiency (FE) reached 46.98% and the current density reached 231.81 mA / cm 2 , significantly exceeding bare copper nanowires (Cu NWs, 25.33%). The Cu-Ni alloy nanowires used in the present invention exhibit excellent stability by virtue of in-situ construction on the gas diffusion electrode, and can operate for more than 8 hours at high current. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is an electron microscope photograph of the Cu-Ni film prepared in Example 1 of the present invention.
[0017] Figure 2 This is an electron microscope photograph of the cross-sectional thickness of the Cu-Ni film prepared in Example 1 of the present invention.
[0018] Figure 3 It is an enlarged cross-sectional view of the Cu-Ni film prepared in Example 1 of the present invention.
[0019] Figure 4 The Cu prepared in Example 1 of the present invention x Ni y (OH) 2 Electron microscope image of nanowires.
[0020] Figure 5 The Cu prepared in Example 1 of the present invention x Ni y (OH) 2 Magnified image of the nanowire.
[0021] Figure 6 The Cu prepared in Example 1 of the present invention x Ni y Electron microscope image of O nanowires.
[0022] Figure 7 3 is an electron microscope photograph of the Cu-Ni nanowires prepared in Example 1 of the present invention.
[0023] Figure 8 is a TEM image of the Cu-Ni nanowires prepared in Example 1 of the present invention.
[0024] Fig. 9 is a HR-TEM image of the Cu-Ni nanowires prepared in Example 1 of the present invention.
[0025] Fig.10 This is a scanning electron microscope and EDS image of the cross section of the Cu-Ni nanowire prepared in Example 1 of the present invention.
[0026] Fig.11 is the XRD spectrum of the Cu-Ni NWs prepared in Example 1 of the present invention.
[0027] Fig.12 is the XRD pattern of Cu (111) peak.
[0028] Fig.13 is the LSV diagram of Cu-Ni NWs prepared in Example 1 of the present invention.
[0029] Fig.14 is the Faradaic efficiency of Cu-Ni NWs.
[0030] Fig.15 is the Faradaic efficiency of Cu NWs.
[0031] Fig.16 is the current density of the Cu-Ni NWs and Cu NWs prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0033] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0034] In the following examples, reagents were used as received without further purification. 4 ,99.99%), nickel sulfate (NiSO 4 ,99.99%), nickel chloride (NiCl 2 ,99.99%), potassium bicarbonate (KHCO 3 ,99.7%), Boric acid (H 3 BO 3 ,99.8%) were provided by Sinopharm Chemical Reagent Company. Sodium sulfate (Na2SO4,99%), sodium hydroxide (NaOH,99%), citric acid (C 6 H 8 O 7 ), ammonium persulfate (NH 4 ) 2 S 2 O 8 ,98%), hydrochloric acid (HCl, AR) and anhydrous ethanol (C 2 H 5 OH). Carbon dioxide (CO 2 , 99.999%), nitrogen (N 2 , 99.999%) and argon (Ar, 99.999%) were used as received. Gas diffusion layer (GDL, hydrophobic carbon paper, Sigracet 22 BB) and anion exchange membrane (3PK-130) were purchased from Gauss Associates. Ultrapure water with a resistivity of 18.45 MΩ cm was prepared in the laboratory.
[0035] In the following examples, the electrochemical test method is as follows: Electrochemical tests were performed in a flow electrolysis cell at ambient temperature. The flow electrolysis cell is a three-electrode cell with three compartments. 3PK-130 was used as an anion exchange membrane separating the anode and cathode, Ag / AgCl electrode (KCl saturated, salt bridge) was used as reference electrode, 1 M KOH was used as electrolyte, iridium oxide mesh (3 × 1 cm) was used as counter electrode, and the working electrode was fixed with a spacer to the size of 2 × 0.5 cm. CO 2It flows into the gas chamber at a rate of 30 sccm and diffuses through the gas diffusion layer into the cathode, where electroreduction occurs at the gas-liquid-solid three-phase interface. The outflowing gas phase products are sampled at fixed intervals (15 min) and quantitatively analyzed using GC. A peristaltic pump is used to assist the circulation of the cathode solution (10 mL / min) and the anode solution (40 mL / min). The electrochemical reaction data are collected using a CHI760E electrochemical workstation, and the Faradaic efficiency of the liquid and gas products is calculated based on the collected charge information (see the test details in the Supporting Information). All electrochemical test experiments use solution resistance to compensate for IR drop, and all potentials are converted to RHE values. Linear sweep voltammetry was performed at a scan rate of 20 mV / s.
[0036] Example 1. Preparation of Cu-Ni NWs A hydrophobic carbon paper (1 × 3 cm) was cleaned with anhydrous ethanol and 0.5 M HCl aqueous solution, respectively. The clean carbon paper was rinsed with ultrapure water and the support layer of the carbon paper was protected with a cover tape. Then, the carbon paper was immersed in 0.1 M CuSO 4 , 0.07 M NiCl 2 , 0.03 M NiSO 4 The mixed solution was added to a solution (0.1 M citric acid buffer) and electrodeposited for 1500 s. The obtained carbon paper covered with Cu-Ni film was thoroughly dried under a nitrogen atmosphere.
[0037] The carbon paper covered with the Cu-Ni film was placed in a solution containing 4.8 g NaOH and 2.282 g (NH 4 ) 2 S 2 O 8 The mixture was then allowed to react at 5 °C for 30 min. After thorough washing and drying, a blue hydroxide was obtained. Subsequently, the sample was annealed in a muffle furnace at 200 °C for 2 h to form a black oxide. In a flowing electrolytic cell, a 0.50 M sodium sulfate solution was used as the electrolyte and a potential of -1.0 V (vs Ag / AgCl sat.KCl) was applied for electrochemical reduction to obtain an in-situ grown Cu-Ni alloy nanowire gas diffusion electrode.
[0038] Example 2. Characterization of Cu-Ni NWs GDE prepared by catalyst ink coating is difficult to utilize its inherent advantages due to CO 2 Problems such as obstructed mass transfer, slow electron transport and insufficient exposure of catalytic active sites lead to CO 2 RR results were poor. In contrast, nanoarray electrodes constructed in situ on GDL can promote rapid CO 2and charge transport, thus significantly enhancing the reaction kinetics.
[0039] In Example 1 of the present invention, a Cu-Ni alloy film is constructed on a GDL by electrodeposition as a precursor of a nanowire structure ( Figure 1 The cross-sectional image shows that the deposited alloy film is distributed on the outer surface of the GDL with a thickness of approximately 6.95 μm ( Figure 2 and Figure 3 ). The continuous and uniform films ensure their electrical connection with the carbon paper substrate. Under alkaline conditions, the Cu-Ni alloy film is converted into Cu x Ni y (OH) 2 Nanowires ( Figure 4 and Figure 5 ). By annealing Cu in a muffle furnace x Ni y (OH) 2 Get Cu x Ni y O nanowires ( Figure 6 Subsequently, CuO was in situ electrochemically reduced to Cu-Ni alloy nanowires (Cu-Ni NWs) in a flow electrochemical cell ( Figure 7 ).
[0040] The one-dimensional linear structure of Cu-Ni NW was confirmed by transmission electron microscopy, and its width was about 65 nm ( Figure 8 ). In addition, HR-TEM shows that Cu NWs are composed of nanocrystals exhibiting different crystal orientations, abundant grain boundaries within the structure indicate that the surface is full of defects, and abundant microporous structures promote CO 2 The mass transfer process ( Fig. 9 ). Cross-sectional SEM image ( Fig.10 ) showed that after nanoscale processing, Cu-Ni NWs were uniformly distributed on the GDL surface without obvious gaps or cracks, showing good adhesion on the GDL substrate. EDS images also supported this result. Compared with the nanowire / GDL electrode prepared by catalyst ink coating, the abundant open spaces between the nanowires in situ constructed on the GDL facilitated the diffusion and adsorption of reactants on the catalyst surface and promoted rapid charge transfer, significantly enhancing the CO 2 RR reaction kinetics.
[0041] The crystal composition of Cu-Ni NWs samples was determined by X-ray diffraction (XRD) patterns ( Fig.11). Cu-Ni NWs exhibit diffraction peaks similar to those of standard copper (ICDD No. 98-000-0172), corresponding to the (111), (200), and (220) planes of copper. Compared with the original Cu NW, the CuO and Cu 2 The peak of O disappears due to the doping of Ni. The more chemically active Ni can prevent the oxidation of Cu NWs, a phenomenon consistent with the behavior observed in Cu-Ni corrosion-resistant alloys.
[0042] In addition, due to the low Ni loading and relatively weak crystallinity, no diffraction data of the Ni phase are shown. Fig.12 In the graph, it is observed that the Cu(111) peak of Cu-Ni NW shifts slightly to a higher diffraction angle and is located between the standard peaks of Cu(111) and Ni(111). This is attributed to the incorporation of Ni atoms into the Cu crystal phase, which produces lattice strain and proves the formation of the alloy.
[0043] Example 3: Cu-Ni NWs electrocatalysis of CO 2 The Cu-Ni NW was loaded onto a flow cell and 1 M KOH was used as the electrolyte to react with CO. 2 Perform electroreduction.
[0044] Before starting the tests, all samples underwent an activation process, which included 20 cyclic voltammetry (CV) from 0 to -1 V (vs. RHE). Cu NWs in situ loaded onto GDL under the same conditions served as a control group for consistent experimental evaluation. Initially, each catalyst was subjected to linear sweep voltammetry in the presence of Ar and CO. 2 atmosphere to ensure a comprehensive analysis.
[0045] like Fig.13 As shown in the figure, it is observed that the reaction start time of Cu-Ni NWs is earlier than that of Cu NWs, and the current density is significantly greater than that of Cu NWs, which indicates that the Cu-Ni NWs of the present invention have a high reaction rate on CO 2 The faster adsorption and electrochemical reaction of the ions promote the accelerated kinetics of CC coupling.
[0046] The efficacy of CO2RR was evaluated by applying electrode potentials ranging from −0.7 V to 1.2 V (vs. RHE). The gas phase products were analyzed by online gas chromatography (GC). The distribution of the main products FE of different catalysts is shown in Figure 2. Fig.14 and Fig.15 Cu-Ni NW achieves the highest C at -1 V 2 H 4 Selectivity (46.98%), current density reached 231.81mA / cm 2 ( Fig.16 ). Cu NWs achieved a carbon product Faradaic efficiency of 56.11% at an applied potential of -1.0 V. However, Cu NWs showed poor selectivity, with relatively uniform distribution of CO (25.62%), CH4 (14.88%), and C2H4 (16.99%), without obvious dominant products, and poor selectivity.
[0047] Compared with the bare Cu NW, the Cu-Ni NW exhibits significantly enhanced C 2 H 4 The selectivity shows the catalytic advantage of alloy nanowires.
[0048] In contrast, the Cu-Ni interface material in thin film form produced only ~18% formate product.
[0049] The Cu-Ni NW three-dimensional nanoarray structure adopted in the present invention provides abundant active sites, greatly enhances the mass transfer process, and promotes the CC coupling kinetics, which is attributed to the synergistic interaction between Cu and Ni atoms, creating a favorable environment for accelerating chemical transformation.
Claims
1. A method for preparing C2H4 by electrochemical reduction of CO2, comprising the following steps: Cu-Ni alloy nanowires were used as gas diffusion electrodes to electrochemically reduce CO2 to C2H4.
2. The method according to claim 1, characterized in that: The electrochemical reduction is carried out in a flow electrolysis cell.
3. The method according to claim 2, characterized in that: The flow electrolytic cell is provided with a three-electrode system, wherein the Ag / AgCl electrode is used as a reference electrode, the iridium oxide mesh is used as a counter electrode, and the Cu-Ni alloy nanowire is used as a working electrode.
4. The method according to any one of claims 1 to 3, characterized in that: The Cu-Ni alloy nanowires are prepared according to a method comprising the following steps: S1, immersing carbon paper in a mixed solution of CuSO4, NiCl2, and NiSO4 for electrodeposition to obtain a Cu-Ni film; S2, the Cu-Ni film reacts under alkaline conditions to obtain Cu-Ni hydroxide nanowires; S3, annealing the Cu-Ni hydroxide nanowires to obtain Cu-Ni oxide nanowires; S4. The Cu-Ni oxide nanowires are electrochemically reduced to obtain in-situ grown Cu-Ni alloy nanowires.
5. The method according to claim 4, characterized in that: In step S1, the mixed solution is prepared by citric acid buffer; In step S1, in the mixed solution, the concentration of CuSO4 is 0.05M-0.15M, the concentration of NiCl2 is 0.03M-0.08M, and the concentration of NiSO4 is 0.03M-0.08M.
6. The preparation method according to claim 4 or 5, characterized in that: In step S1, the electrodeposition time is 1500-2000s.
7. The method according to any one of claims 4 to 6, characterized in that: In step S2, the alkaline condition is an aqueous solution of NaOH and (NH4)2S2O8, the concentration of NaOH is 45-50 g / L, and the concentration of (NH4)2S2O8 is 20-25 g / L.
8. The method according to any one of claims 4 to 7, characterized in that: In step S2, the reaction temperature is 2-8°C and the reaction time is 0.3-0.6h.
9. The method according to any one of claims 4 to 8, characterized in that: In step S3, the annealing temperature is 150-200° C. and the time is 0.5-2 h.
10. The method according to any one of claims 4 to 9, characterized in that: In step S4, the electrochemical reduction is performed in a flowing electrolytic cell using a sodium sulfate solution as an electrolyte.
Citation Information
Patent Citations
Electrochemical CO2 reduced tin modified copper nanowire electrode and preparation method thereof
CN115928121A
Preparation method and application of nickel-modified copper-based monatomic alloy oxide nanowire
CN118292028A
Electrochemical reduction of CO2 to CH4 and C2H4
US4897167A